Design for assembly and application using Hitachi assemblability evaluation method - Mohd Naim, Zakaria (2009)
This project is described about application of Hitachi Assemblability Method (AEM) in Design for Assembly. Using this method, in the early design stage, product design quality is analyzed quantitatively and weakness in the design’s assembly producibility are highlighted. The AEM is belongs to class of “point of” methods. The “perfect” part or assembly operation gets the maximum score, usually one hundred, and each element or difficulty is assigned a penalty. The main objective of this project are to determine and calculate the score of AEM for part (Ei) and the product AEM (E¬) score and also to redesign the current design using application of Hitachi Assemblability Evaluation Method(AEM). Mini radio was chosen as a product in order to accomplish the objective of Design for Assembly using application of Hitachi Assemblability Evaluation Method. The product was chosen because it has a high demand in the market. The mini radio need to disassemble to identified total number of part that contains to produce a whole mini radio. The disassemble part then, need to modeling in 3D using solidworks to show the explode view of the product. Improvement of product (redesign) also need to modeling in 3D using solidworks. Calculate of the score for reducing part and also the whole product by adding up the penalty for each process. The score need to do judgment either it obey the desirable value (above 80) or not. The score of AEM for part and product need to tabulate to give a clear view in order to achieve the main objective of this project to come out with the score. From this project, the component of mini radio have been reduce from 21 part to 16 part by combining some component that made from same material and not necessary component become one part. The assembly efficiency also has increase after modification. The significance of this project is, AEM score part and product can be determined and some of unknown penalty can be determine by reverse calculation. Enable to reduce part attaches in assembly process using application of Hitachi Assemblability Evaluation Method.